Introducing an Application of a Charged Coupled Device (CCD) in an Optical Tomography System - Juliza Jamaludin; Rahim, RA; Rahim, HA; Rahiman, HF; Muji, SZM; Fadzil, NSM; Ling, LP; Jumaah, F; Ahmad, A; Ayob, NMN; Hong, LE (Penerbit UTM Press, 2024)
Indexed by WOS/SCOPUS